2005
DOI: 10.1534/genetics.104.039263
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Repeatable Elimination of a Parental Genome-Specific DNA Repeat (pGc1R-1a) in Newly Synthesized Wheat Allopolyploids

Abstract: Recent work in the Triticum-Aegilops complex demonstrates that allopolyploidization is associated with an array of changes in low-copy coding and noncoding sequences. Nevertheless, the behavior and fate of repetitive DNA elements that constitute the bulk of nuclear DNA of these plant species is less clear following allopolyploidy. To gain further insight into the genomic events that accompany allopolyploid formation, we investigated fluorescence in situ hybridization (FISH) patterns of a parental-specific, tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 61 publications
(16 reference statements)
5
94
2
2
Order By: Relevance
“…It should be pointed out that some of the previously uncovered rapid genomic changes associated with wheat allopolyploidization such as elimination of coding and noncoding sequences have been documented as highly reproducible in randomly chosen individuals from multiple independently formed lines (Feldman et al 1997;Liu et al 1998a,b;Ozkan et al 2001;Han et al 2005). Therefore, this type of rapid genetic instability likely has played some roles in the initial establishment and eventual speciation of T. aestivum (Levy and Feldman 2004;Feldman and Levy 2005;Feldman and Levy 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be pointed out that some of the previously uncovered rapid genomic changes associated with wheat allopolyploidization such as elimination of coding and noncoding sequences have been documented as highly reproducible in randomly chosen individuals from multiple independently formed lines (Feldman et al 1997;Liu et al 1998a,b;Ozkan et al 2001;Han et al 2005). Therefore, this type of rapid genetic instability likely has played some roles in the initial establishment and eventual speciation of T. aestivum (Levy and Feldman 2004;Feldman and Levy 2005;Feldman and Levy 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies employing newly synthesized allopolyploid wheat lines have documented that the onset of both the tetra-and hexapolyploidization events is associated with rapid and extensive structural genomic instabilities including elimination of coding and noncoding sequences (Feldman et al 1997;Liu et al 1998b;Ozkan et al 2001;Han et al 2005) and changes in DNA methylation (Liu et al 1998a;Shaked et al 2001). Nonetheless, analysis at many unbiased loci from a genome-wide perspective was conducted thus far only at the tetraploid level (Shaked et al 2001;Qi et al 2010), while either only a few preselected loci known to be labile (chromosome-and genome-specific sequences) or a set of selected microsatellite loci have been investigated at the hexaploid level to detect allohexaploidy-associated rapid genomic changes (Feldman et al 1997;Liu et al 1998a,b;Ozkan et al 2001;Mestiri et al 2010).…”
mentioning
confidence: 99%
“…Similarly, He et al (2003) underlined the nonrandom feature of gene expression alterations in synthetic and natural hexaploid wheat. Recently, Han et al (2005) demonstrated that a tandem DNA repeat was reproducibly lost in three sets of newly synthesized TriticumAegilops allopolyploids. On the other hand, Wang et al (2004Wang et al ( , 2006 inferred stochastic changes of gene expression in A. suecica allotetraploids.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the genomic changes observed in recent allopolyploids, such as in Tragopogon miscellus (Chester et al, 2012), Brassica napus (Gaeta et al, 2007;Szadkowski et al, 2010;Xiong et al, 2011), or cotton (Gossypium hirsutum; Flagel et al, 2012), are consistent with homoeologous exchanges. In other cases, the observed genomic changes may have a different origin, such as some of the changes reported in wheat (Triticum aestivum; Feldman et al, 1997;Han et al, 2005;Zhang et al, 2013). Furthermore, rapid changes did not ensue in newly synthesized allotetraploid cotton (Liu et al, 2001;Xiong et al, 2011), suggesting that different allopolyploids might respond differently to the challenge.…”
Section: Introductionmentioning
confidence: 93%